Researching the transparency of personal data sharing: designing a concert receipt - Styliari, Tatiana C.; Nati, Michele (Digital Catapult, 2016)
The project’s overarching aim was to increase people’s awareness, trust and control over the data that they share with organisations and explore how organisations can give more control over the data individuals share when conducting personal data transactions. We focused on personal data sharing and trust using user experience (UX) design and prototyping methodology.